Problematika Perundingan Perjanjian Kerja Bersama Antara Pengusaha dengan Serikat Pekerja dalam Rangka Mewujudkan Kepastian Hukum (Ditinjau dari Undang-Undang Nomor 6 Tahun 2023 Tentang Cipta Kerja) - Suryanto, Tri; Santoso, Imam Budi; Tinambunan, Wahyu Donri (Universitas Batanghari Jambi, 2024)
The implementation of Law Number 6 of 2023, which pertains to Job Creation, has ushered in notable transformations within the employment landscape. The negotiation process for Collective Labor Agreements frequently embodies a complex interplay and conflict of interests between employers and labor unions. Following the implementation of the Job Creation Law, there has been a noticeable widening of disparities in the negotiation content for Collective Labor Agreements. Numerous instances have been observed where negotiations falter and fail to culminate in an agreement before the expiration of the deadline. This study is conducted using a normative juridical approach, focusing on legal analysis through the examination of library resources or secondary data. This study employs an analytical descriptive approach, aimed at offering a detailed examination of the subject matter through the analysis of collected data or samples. This method is particularly applied to explore the dynamics of Collective Labor Agreement negotiations involving employers and trade unions. The investigation took place at PT Astra Nippon Gasket Indonesia, located in Karawang Regency. What influences collective labor agreement negotiations to be hampered are internal factors (differences in interests, wages, termination of employment, inequality and discrimination, changes in policies or working conditions, and trade union membership) and external factors (company intervention, workload, laws and regulations). Consequences if the Collective Work Agreement negotiations are not completed by the agreed time limit and it turns out that no agreement (deadlock) has been reached regarding the substance of the new PKB (next period), then based on Article 123 paragraph (4) UUK by law the PKB currently in force remains in effect for a period of time. a maximum of 1 (one) year. PKB is not just an agreement (in the company), but in time it will become a norm and customary law in a certain scope (contractualist model). In this case, statutory regulations provide legitimacy (binding legal force) for a PKB to remain valid as a custom within the specified period.